2007
DOI: 10.2174/138920007780655441
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Cryptotanshinone, a Major Active Triterpenoid in Salvia Miltiorrhiza Bunge Widely Used in the Treatment of Stroke and Alzheimers Disease, Across the Blood-Brain Barrier

et al.

Abstract: Cryptotanshinone (CTS), a major constituent from the roots of Salvia miltiorrhiza (Danshen), is widely used in the treatment of coronary heart disease, stroke and less commonly Alzheimer's disease. Our recent study indicates that CTS is a substrate for P-glycoprotein (PgP/MDR1/ABCB1). This study has investigated the nature of the brain distribution of CTS across the brain-blood barrier (BBB) using several in vitro and in vivo rodent models. A polarized transport of CTS was found in rat primary microvascular en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 30 publications
1
45
0
Order By: Relevance
“…brovascular diseases for decades (Wu et al, 1998;Ling et al, 2005;Cheng, 2007;You et al, 2007;De Palma et al, 2008;Han et al, 2008). The other major constituents of Salvia miltiorrhiza roots as the lipophilic diterpenoid quinines (tashinones) (De Palma et al, 2008), now available in the form of standardized TTE-50 extract (Sun et al, 2007), have recently been demonstrated to exert their effects in preventing aging and Alzheimer's disease via an antioxidant pathway (Yu et al, 2007) and decreasing matrix metalloproteinases activity on diet induced atherosclerosis (Fang et al, 2008). In the present study, we evaluated the protective effects of single-and polyphenol containing aqueous SMAE against Hcy-induced oxidative damage exerted on the cultured rat aortic smooth muscle A10 cells, which were used as the in vitro SMCs model.…”
Section: Discussionmentioning
confidence: 99%
“…brovascular diseases for decades (Wu et al, 1998;Ling et al, 2005;Cheng, 2007;You et al, 2007;De Palma et al, 2008;Han et al, 2008). The other major constituents of Salvia miltiorrhiza roots as the lipophilic diterpenoid quinines (tashinones) (De Palma et al, 2008), now available in the form of standardized TTE-50 extract (Sun et al, 2007), have recently been demonstrated to exert their effects in preventing aging and Alzheimer's disease via an antioxidant pathway (Yu et al, 2007) and decreasing matrix metalloproteinases activity on diet induced atherosclerosis (Fang et al, 2008). In the present study, we evaluated the protective effects of single-and polyphenol containing aqueous SMAE against Hcy-induced oxidative damage exerted on the cultured rat aortic smooth muscle A10 cells, which were used as the in vitro SMCs model.…”
Section: Discussionmentioning
confidence: 99%
“…There are various in vitro and in vivo studies that have suggested that Dan Shen improves microcirculation, dilates the coronary arteries, possesses anti-arthrosclerotic properties, and prevents myocardial necrosis under ischemic states [8]. It is also a Chinese herb commonly included in prescriptions to treat AD [9]. In a recent study using high fat diet (HFD) fed rats, we have demonstrated that a Chinese herbal extract, containing S. miltiorrhiza and Gardenia jasminoides (coded SK0506), reduced central obesity, lowered triglycerides and free fatty acid levels in the blood stream and prevented TG deposition in liver and skeletal muscles [10].…”
Section: Abbreviationsmentioning
confidence: 99%
“…It can cross the blood-brain barrier and improve the cognitive deficits in mice [13], and provide beneficial effects in stroke and ischaemic diseases [14], with few or no side effects. CTS has been suggested to be a leading compound for drug development to treat AD [15].…”
Section: Introductionmentioning
confidence: 99%